2002
DOI: 10.1038/sj.neo.7900234
|View full text |Cite
|
Sign up to set email alerts
|

IL-13Rα2 is a Glioma-Restricted Receptor for Interleukin-13

Abstract: We have found that binding sites for interleukin-13 (IL-13) are overexpressed in a vast majority of high-grade astrocytomas (HGAs). These binding sites for IL-13 are distinct from the physiological receptor in that it does not bind IL-4. We also demonstrated that IL-13 receptor alpha 2 protein chain (IL-13Ralpha2), an IL-4-independent receptor for IL-13, is abundant among HGAs, but not in normal organs. To examine if IL-13Ralpha2 is the tumor-associated site for IL-13, we stably transfected normal Chinese hams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
109
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 22 publications
1
109
0
Order By: Relevance
“…Previous studies have demonstrated that the attachment of radiolabeled IL-13 to the functional heterodimer receptor can be competed by IL-4 as well as IL-13, [30][31][32]49 whereas its attachment to IL-13R 2 is competed by IL-13 but not IL-4. 2,9,10,15,33,36 To confirm that the cytotoxicity of IL-13 cytotoxin was specifically mediated through IL-13R 2 chain delivered by Ad-IL-13R 2 vector, A549 cells were infected with Ad-IL-13R 2 at MOI 10 followed by treatment with IL-13 cytotoxin (10 ng/ml) in the presence of a 50-fold dose of human IL-13 or IL-4. As shown in Figure 4, IL-13 and IL-4 did not affect the growth of uninfected or Ad-LacZ-infected cells, regardless of treatment with IL-13 cytotoxin.…”
Section: Il-13 But Not Il-4 Competitively Inhibits Cytotoxicity Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the attachment of radiolabeled IL-13 to the functional heterodimer receptor can be competed by IL-4 as well as IL-13, [30][31][32]49 whereas its attachment to IL-13R 2 is competed by IL-13 but not IL-4. 2,9,10,15,33,36 To confirm that the cytotoxicity of IL-13 cytotoxin was specifically mediated through IL-13R 2 chain delivered by Ad-IL-13R 2 vector, A549 cells were infected with Ad-IL-13R 2 at MOI 10 followed by treatment with IL-13 cytotoxin (10 ng/ml) in the presence of a 50-fold dose of human IL-13 or IL-4. As shown in Figure 4, IL-13 and IL-4 did not affect the growth of uninfected or Ad-LacZ-infected cells, regardless of treatment with IL-13 cytotoxin.…”
Section: Il-13 But Not Il-4 Competitively Inhibits Cytotoxicity Of mentioning
confidence: 99%
“…Previous studies have proved that IL-13 cytotoxin is highly selective and potent in killing cancer cells that overexpress IL-13R 2 chain. 3,[5][6][7][8][9][10][11][12]14,16,17 Preclinical studies regarding the safety and toxicity of IL-13 cytotoxin have been performed in mice, rats and monkeys; and all animals tolerated this therapy well, with minimal toxicity to vital organs. 18 Based on these results, 3 phase I/II clinical trials of this cytotoxin in adults with malignant glioma have been initiated, and all are currently ongoing in the United States.…”
mentioning
confidence: 99%
“…We discovered that interleukin 13 receptor alpha 2 (IL-13RA2) and EphA2 receptor are overexpressed in most patients with GBM, but not in normal brain (27)(28)(29)(30)(31), and also in spontaneous canine GBM, an excellent translational model of GBM (32)(33)(34)(35). Expression of IL-13RA2 and EphA2 is partially overlapping; hence, the combined overexpression is ~90% in patients with GBM (31).…”
Section: Targeted Cytotoxic Therapy Of Gbmmentioning
confidence: 99%
“…27 This protein binds IL-13, but does not bind 29 Studies have shown that malignant glioblastomas overexpress this restricted receptor for IL-13, and that IL-13Ra2 is the molecular entity responsible for IL-13 binding to glioblastoma tumors. 7,8,12,30,31 An IL-13-based Pseudomonas exotoxin A (PE) fusion protein (FP) showed promising clinical antitumor activity, but no toxicity to normal endothelial, lymphoid, or bone marrow precursor cells. 32 DT and PE have identical mechanisms of action and are known to induce cell death with as little as 1 toxin molecule.…”
mentioning
confidence: 99%
“…[6][7][8] Targeting the IL-13 receptor with an immunotoxin (IT) has already proven to have potential for treating brain tumors. [8][9][10][11][12] ITs are not mainstream pharmaceuticals, and treatment of systemic tumors with ITs has been limited by their failure to localize in tumor. The promise of these drugs is considerably greater for brain-cancer therapy, since IT can be directly administered intracranially.…”
mentioning
confidence: 99%